2008
DOI: 10.1016/j.fertnstert.2007.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of amlodipine on ischemia-reperfusion injury of rat ovary: biochemical and histopathologic evaluation

Abstract: Conservative treatment with amlodipine is effective in reducing tissue damage induced by ischemia, I/R, or both in ovaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 35 publications
7
71
0
Order By: Relevance
“…Pretreatment with amlodipine markedly reduced the MDA content as compared to the I/R group, suggesting that amlodipine inhibits lipid peroxidation and protects the tissue against free radical damage. These findings are in agreement with previously published studies concluding that amlodipine reduces oxidative stress and protects against lipid peroxidation in cell membranes, a likely contributor to the cell death observed after I/R [13]. GSH plays a principal role in the cellular, protective system against toxic, free radical-induced tissue injury [31], and depletion of GSH increases the chance of free radical-induced damage [32].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Pretreatment with amlodipine markedly reduced the MDA content as compared to the I/R group, suggesting that amlodipine inhibits lipid peroxidation and protects the tissue against free radical damage. These findings are in agreement with previously published studies concluding that amlodipine reduces oxidative stress and protects against lipid peroxidation in cell membranes, a likely contributor to the cell death observed after I/R [13]. GSH plays a principal role in the cellular, protective system against toxic, free radical-induced tissue injury [31], and depletion of GSH increases the chance of free radical-induced damage [32].…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies, we demonstrated that amlodipine exerts anti-inflammatory, anti-osteoporotic, and protective effects against ovarian ischemia-reperfusion (I/R) damage [12,13]. Amlodipine has also been clinically and experimentally shown to have antiatherogenic effects because it decreases and/or blocks inflammation from forming in the atheroma plaques on the vascular endothelium by inhibiting nitric oxide synthase activity [14].…”
Section: Introductionmentioning
confidence: 99%
“…They include vascular congestion, atretic follicles, haemorrhage, edema and inflammatory cells infiltration (Coskun, et al, 2007;Guven et al, 2008;Halici et al, 2008). In this study, although not all the classical features of oxidativestress induced histopathological changes were observed however, it cannot be completely excluded that the ovary may be under some form of oxidative stress.…”
Section: Discussionmentioning
confidence: 52%
“…Hypoxia generally impairs intracellular Ca +2 homeostasis and leads to various pathological situations such as neuronal cell damage, neurodegeneration, and cell death. The damage that occurs varies as a function of the duration of hypoxia as a result of ischemia according to fetal age [14][15][16]. We demonstrated that the survivals rates of infant rats born to rats with torsio/detorsio uteri were decreased.…”
Section: Metagenomic Sequencingmentioning
confidence: 83%